Outcome of Intra-Articular Steroid Injection in Osteoarthritis of Knee: A One Year Experience - Al Hasan, Suzon; Siddiq, Md Abu Bakar; Rahim, Md Abdur; Shakoor, Md Abdus; Paul, Sujat; Salek, AKM; Khan, Md Moniruzzaman; Ahmed, Syed Mozaffar; Hossain, Md Shawkat; Dutta, Nitai Prasad; Chowdhry, Sumit Roy; Karim, Sifat Binte; et al. (Journal of Chittagong Medical College Teachers' Association, 2010)
Keywords: osteoarthritis of knee; intra-articular steroid; outcome DOI: 10.3329/jcmcta.v20i2.5624 Journal of Chittagong Medical College Teachers' Association 2009: 20(2):33-38